Importance of nutrition in achieving the millennium development goals - Khor, Geok Lin (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2008)
The Millennium Development Goals (MDGs) provide a global agenda for the international and national agencies and non-government organisations to work together towards promoting human development as the key to sustaining social and economic progress. There are eight MDGs to be achieved by the year 2015: Goal 1- Eradicate extreme poverty and hunger; Goal 2 - Achieve universal primary education; Goal 3- Promote gender equality and empower women; Goal 4- Reduce child mortality; Goal 5- Improve maternal health; Goal 6- Combat HIV/AIDS, malaria and other diseases; Goal 7- Ensure environmental sustainability; and Goal 8- Develop a global partnership for development. Each MDG b is accompanied by one or more targets, which in turn are monitored by specific measurable indicators. Several of these indicators are closely linked to nutrition, thus underscoring the paramount importance that nutrition plays in influencing the success of the MDGs, especially those aimed at reducing hunger and poverty, improving education attainment, gender equality, child mortality, maternal health and combating diseases. Adequate nutrition including key micronutrients is crucial for optimum growth and development from infancy through childhood and adolescence. Improving maternal health is also critical as impaired health during pregnancy can bring about an inter-generational effect on human capital. Gender equality is said to bring about a 'double dividend' in benefiting both women and children. Access to safe water and living in a sanitary environment are necessary conditions for ensuring people do not run the risk of infections and diseases arising from an unclean environment. Incorporating nutrition considerations into government development policies and budgets is essential towards enhancing the achievement of the health-related MDGs by 2015.